ANALISIS PENGGUNAAN KOSAKATA PROFANITI DALAM FILM AMERICAN PIE 7 â€œBOOK OF LOVEâ€ - Nangune, Lidia Mayasari (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT The title of this study is ‘An Analysis of Using Profanity Words in the Movie American Pie 7 Book of Love’. This research is an attempt to identify, describe and analyze profanity words by using theory of Pattridge (1984). In collecting the data, the writer pays close attention to use of profanity words in the film. The words of profanity are collected by watching the whole movie, and then analyzed them in terms of their forms and pattern to find out the meaning of using profanity words in every conversation on the movie American Pie 7 Book of Love. The result of this research shows that profanity words are usually used to express their feeling. Profanity words are not only used at the bad situation like angry, but also in enjoying time to express happiness.